The development of the relationship model of causal factors affecting the financial report quality and financial success of small and medium sized hotel business in Thailand (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research is a mixed research with the objective of develop a causal factor correlation model. And examining the consistency of the relationship model, causal factors affecting the quality of financial reports and financial success of small and medium-sized hotel businesses in Thailand. Developed according to theory and empirical data. The sample group was accounting and finance executives of small and medium-sized hotel businesses in Thailand. The research tool was a questionnaire. Statistics used in the analysis of structural equation Model data and in-depth interview. The research results for the quality of financial reports had a direct correlation with professional accounting skills, coefficient of 0.27, ethics in accounting profession, coefficient at 0.50 and management of accounting department.  The coefficient of 0.32 for financial success had a direct correlation with the quality of financial reports 0.40, management of accounting department 0.51 and was indirectly related to professional accounting skills, coefficient of 0.11, ethics in accounting profession, coefficient of 0.20 by Pass the quality of financial reports and it has been confirmed that the model has become possible between a developed small and medium hotel business